1980
DOI: 10.1172/jci109987
|View full text |Cite
|
Sign up to set email alerts
|

A new role for complement in experimental membranous nephropathy in rats.

Abstract: A B S T R A C

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
121
0
4

Year Published

1986
1986
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(132 citation statements)
references
References 29 publications
7
121
0
4
Order By: Relevance
“…These models display many features of human disease (5) and have substantially contributed to our current understanding of the disease. PHN is induced by injection of heterologous antiserum from sheep immunized with a crude extract of proximal tubular brush border from rat kidney (4). One target of this antiserum is megalin, which is localized on the basal surface of podocyte foot processes in rats (6,7).…”
mentioning
confidence: 99%
“…These models display many features of human disease (5) and have substantially contributed to our current understanding of the disease. PHN is induced by injection of heterologous antiserum from sheep immunized with a crude extract of proximal tubular brush border from rat kidney (4). One target of this antiserum is megalin, which is localized on the basal surface of podocyte foot processes in rats (6,7).…”
mentioning
confidence: 99%
“…Moreover, we found that the anti nephritic effect of OB-5 on accelerated passive Heymann nephritis (APHN) was also less than that on crescentic-type nephritis (unpublished data of T. Hat tori et al). It has been believed that the induction and development of APHN are not mediated by leukocyte infiltration into glomeruli, and it may depend on the antibody formation against heterologous antigens (21,22). In addition, we also found that the numbers of cytotoxic T cells, macrophages, la antigen and IL-2 receptor-positive cells in the glomeruli of APHN rats was not higher than those of normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…Salant и соавт. [23]. Предварительное подавление общей активности комплемента у лабораторных крыс путем введения им яда кобры предупреждало развитие протеину-рии при последующем воспроизведении у них Хеймановского нефрита, несмотря на образова-ние в клубочках субэпителиальных депозитов.…”
Section: участие системы комплемента в патогенезе мембранозной нефропunclassified